1987
DOI: 10.1128/aac.31.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of bone, joint, and soft-tissue infections with oral ciprofloxacin

Abstract: We treated 52 patients with orally administered ciprofloxacin. In this study of 34 men and 18 women who completed therapy and who could be evaluated, there were 29 patients with nonhematogenous osteomyelitis, 20 patients with skin or soft-tissue infections, and 3 patients with joint infections. During the study, 92 isolates of pathogenic facultative aerobic bacteria, including 37 members of the family Enterobacteriaceae, 30 Staphylococcus aureus isolates, and 21 Pseudomonas aeruginosa isolates, were recovered,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 18 publications
4
62
0
Order By: Relevance
“…Although this result was formally statistically insignificant, we detected this tendency in all analyses performed. Our failure risk of 24% is congruent with the 20% [12], 21% [13], 25% [27], 27% [14] or 30% [9] failure rates reported for pseudomonal osteoarticular infections, although lower (5% [11]; 7% [21]) or higher failure rates ranging from 33% [23], 35% [24], 38% [22] to 39% [15] also exist in small case series from the 1980s. Development of resistance among failure cases to the antimicrobial agents used during therapy occurred in 15%, which is congruent with the 13-24% risk after a prolonged antibiotic monotherapy during three-four months [9,24].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Although this result was formally statistically insignificant, we detected this tendency in all analyses performed. Our failure risk of 24% is congruent with the 20% [12], 21% [13], 25% [27], 27% [14] or 30% [9] failure rates reported for pseudomonal osteoarticular infections, although lower (5% [11]; 7% [21]) or higher failure rates ranging from 33% [23], 35% [24], 38% [22] to 39% [15] also exist in small case series from the 1980s. Development of resistance among failure cases to the antimicrobial agents used during therapy occurred in 15%, which is congruent with the 13-24% risk after a prolonged antibiotic monotherapy during three-four months [9,24].…”
Section: Discussionsupporting
confidence: 65%
“…P. aeruginosa accounts for an absolute minority of all osteoarticular pathogens [1], and most reports are either case series involving around 20-30 cases [9][10][11][12][13] or even less [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Moreover, these reports subsume P. aeruginosa under other Gram-negative pathogens [9,12,13,19], including anaerobes [10,28], and lack adjustment for case mix [9,10,19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Greenberg et al [23] reported that none of six patients with osteomyelitis caused by Staphylococcus aureus (monoculture) was cured with ciprofloxacin therapy.…”
Section: Antibiotic Discussionmentioning
confidence: 99%
“…39 S salivarius bacteremia has also been reported during ciprofloxacin therapy for osteomyelitis. 40 Therefore, treatment as well as prophylaxis with ciprofloxacin may not prevent future episodes of S salivarius SBP. On the other hand, gatifloxacin has been reported to be highly active in vitro against VGS isolates.…”
Section: Discussionmentioning
confidence: 99%